2002
DOI: 10.1080/13698570220137024
|View full text |Cite
|
Sign up to set email alerts
|

Coronary heart disease: Women's assessment of risk--a qualitative study

Abstract: Coronary heart disease (CHD) kills over 135,000 people each year. The underlying premise of this study was that women might not assess themselves as at risk because CHD has generally been perceived within popular culture, medicine and research as a man's disease. Hayes (Social Science and Medicine, 35, pp. 55-61, 1991) suggests that critical to the success of any risk assessment strategy is: the identi cation of risk markers that can accurately predict speci c adverse health outcomes and the ability of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 16 publications
1
31
1
2
Order By: Relevance
“…Referral and regular monitoring in a specialist clinic may have modified our participants' notions of risk factors for CHD. Our findings are in accordance with previous research on the lay epidemiology of CHD [5,6,8] but our participants seem to be relatively more doubtful about how valid and useful their notions of the coronary candidate are [5,6,8]. An explanation for this may be that they have been diagnosed with a hereditary condition and therefore consider themselves as atypical in relation to the public imagery of likely victims of CHD.…”
Section: Validity and Transferabilitysupporting
confidence: 82%
See 1 more Smart Citation
“…Referral and regular monitoring in a specialist clinic may have modified our participants' notions of risk factors for CHD. Our findings are in accordance with previous research on the lay epidemiology of CHD [5,6,8] but our participants seem to be relatively more doubtful about how valid and useful their notions of the coronary candidate are [5,6,8]. An explanation for this may be that they have been diagnosed with a hereditary condition and therefore consider themselves as atypical in relation to the public imagery of likely victims of CHD.…”
Section: Validity and Transferabilitysupporting
confidence: 82%
“…Research indicates that the candidate for CHD is often portrayed as a man [7Á9], and that women with symptoms of CHD appear to adopt risk assessment strategies that enable them conceptually to distance themselves from risk of CHD by attributing risky lifestyle behaviour to men [5]. A better understanding of how patients at risk of CHD Correspondence: Jan C. Frich, Institute of General Practice and Community Medicine, University of Oslo, P.O.…”
mentioning
confidence: 99%
“…91,102 Studies have found that women tended to view exercise primarily in terms of losing weight and keeping fit and mobile rather than in terms of CVD prevention. 38,106 It has also been found that women tended to perceive that the activity inherent in their domestic lives provided moderate physical activity, which may be considered to be best because overexercising may be considered potentially harmful. 106,107 Research has also pointed to insufficient information being given to patients about lifestyle modification 77,91,100,108 or found that they have insufficient knowledge to be able to make lifestyle changes.…”
Section: Patient Perspectives On Lifestyle Modification Recommendationsmentioning
confidence: 99%
“…For example, Ruston and Clayton found that, despite the presence of known risk factors, their women participants did not tend to view themselves as being at risk unless they adopted a "man's way of life". 38 Studies have also looked at how factors such as family history of CVD, ethnicity, stress and hypercholesterolemia, affect people's perceived risk. These study populations typically also had significant knowledge of modifiable risk factors for CVD, which was likewise incorporated within lay epidemiology regarding their own risk.…”
mentioning
confidence: 99%
“…Health promotional adverts and the media urge us to be aware of ever more risk factors for future disease (Ruston and Clayton, 2002). Critics of a preventive medicine based on risk factors have argued that this focus on risk may lead to 'surveillance medicine', with the body permanently at risk, needing monitoring and intervention (Armstrong, 1995).…”
Section: Worrying About the Futurementioning
confidence: 99%